2015
DOI: 10.1021/jacs.5b06835
|View full text |Cite
|
Sign up to set email alerts
|

Giant Rugby Ball [{CpBnFe(η5-P5)}24Cu96Br96] Derived from Pentaphosphaferrocene and CuBr2

Abstract: The self-assembly of [CpBnFe(η5-P5)] (CpBn = η5-C5(CH2Ph)5) with CuBr2 leads to the formation of an unprecedented rugby ball-shaped supramolecule consisting of 24 units of the pentaphosphaferrocene and an extended CuBr framework, which does not follow the fullerene topology. The resulting scaffold of 312 noncarbon atoms reveals three different coordination modes of the cyclo-P5 ligand including a novel π-coordination. The outer dimensions of 3.7 × 4.6 nm of the sphere approach the range of the size of proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…This single result led to some decisive questions as to whether the concept of structural arrangements of four‐ and six‐membered rings in supramolecules could be extended to unprecedented spherical structural motifs as it was possible for the five‐membered ring of pentaphosphaferrocene 2, 7. Moreover, further information on the formation process and the structural stability in solution was required as the insolubility of the formerly obtained 32‐vertex ball 2 a did not allow for any investigations of its behavior in solution.…”
mentioning
confidence: 99%
“…This single result led to some decisive questions as to whether the concept of structural arrangements of four‐ and six‐membered rings in supramolecules could be extended to unprecedented spherical structural motifs as it was possible for the five‐membered ring of pentaphosphaferrocene 2, 7. Moreover, further information on the formation process and the structural stability in solution was required as the insolubility of the formerly obtained 32‐vertex ball 2 a did not allow for any investigations of its behavior in solution.…”
mentioning
confidence: 99%
“…In recent decades, the evolution of E n ligand complexes( E= P, As) that are isolobal to well-known organic molecules impressively exemplifiedt he inseparability of organic and inorganic chemistry. [1][2][3] Besides their rich coordination chemistry [4] including dynamic complexes, [5] polymers, [6,7] and fullerene-like nanospheres, [8,9] our group is especially interested in the unique reactivity of these E n ligand complexes and the comparison to their organic analogs.I tw as shown that the ferrocene analogous complex [Cp*Fe(h 5 -P 5 )] readily reacts with main group nucleophiles underb ond formationa nd rearrangemento ft he planar cyclo-P 5 ligand to an envelope conformation. [10] Additionally,[ Cp*Fe(h 5 -P 5 )] exhibits ad istinctly different redox behavior than ferrocene, with single-electron oxidation as well as reduction,r esulting in dimerization through PÀPb ond formation.…”
mentioning
confidence: 99%
“…This overall number of P 5 units in the sphere is exceptional because fullerene-like speciesu sually contain 12 cyclo-P 5 ligands. [4] There is only one CuBr-containing supramolecule knownw ith 24 units of 1a, [17] and anothero ne, however CuI-based, with 10 P 5 rings, possessing ac ube-like scaffold (Figure 1c). [4c] The CuBr scaffoldi n4 consists of as everely disordered middle framework with the sum composition of Cu 16.…”
Section: Resultsmentioning
confidence: 99%